Comparative study of pear drying using solar stove and tunnel drying - Guiné, Raquel (2013)
Sun-dried pears of Portuguese S. Bartolomeu variety are relatively small fruits with peculiar organolephtic characteristics. The open sun drying has some disadvantages related with drying efficiency and food safety. However the drying with an economic and friendly energy is an important characteristic of the drying methods and therefore several attempts have been made to develop processes using solar drying. The present work studies two types of pears drying, namely solar stove and tunnel drying, using the solar energy and simultaneously reducing the exposure of fruits to contamination agents. Both processes were conducted in two consecutive years to analyse if the behaviour of each drying method shows evidence of a similar pattern. The results enable us to conclude that the variation of normalized moisture of pears with the drying time follows a linear relationship while an exponential decay is observed in the tunnel drying. Despite the different climatic conditions, it is possible still to observe that the behavior of each process is quite similar in both consecutive years. However, in the year of 2008 the drying tends to be faster in both processes. In addition, it is also possible to conclude that the Total Soluble Solids/Acidity ratio has a similar behavior along the drying in the two years for each process. However, the decrease of acidity of pears in solar stove is more pronounced than the TSS and consequently a higher ratio of Total Soluble Solids/Acidity is observed along the solar stove drying when compared with the tunnel drying.